2011
DOI: 10.1002/adma.201102019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a New Two‐Dimensional C4H‐Type Polymer Based on Hydrogenated Graphene

Abstract: A new polymer with C4H stoichiometry based on graphene is synthesized in situ using template‐induced polymerization of self‐organizing hydrogen adsorbates on graphene. The polymerization is observed “live” on the surface of graphene by photoemission spectroscopy. Photoemission spectroscopy allows for an accurate determination of the carbon/hydrogen stoichiometry, an aspect that is extremely important for understanding functionalized graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
143
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(159 citation statements)
references
References 47 publications
14
143
2
Order By: Relevance
“…Judging from the size of a band gap and the temperature-dependent resistivity of our H-Gr showing an η of 25%, we have reached the conclusion that our saturated H-Gr can have a form of para-type C 4 H (refs 31, 32, 33), a single-sided hydrogenated graphene. As a matter of fact, hydrogenation in the H-Gr happens most probably on the top surface of graphene transferred onto a SiO 2 /Si substrate, because our hydrogen atoms do not have strong enough energy to penetrate graphene due to the mild and non-destructive nature of indirect hydrogen plasma.…”
Section: Resultsmentioning
confidence: 68%
“…Judging from the size of a band gap and the temperature-dependent resistivity of our H-Gr showing an η of 25%, we have reached the conclusion that our saturated H-Gr can have a form of para-type C 4 H (refs 31, 32, 33), a single-sided hydrogenated graphene. As a matter of fact, hydrogenation in the H-Gr happens most probably on the top surface of graphene transferred onto a SiO 2 /Si substrate, because our hydrogen atoms do not have strong enough energy to penetrate graphene due to the mild and non-destructive nature of indirect hydrogen plasma.…”
Section: Resultsmentioning
confidence: 68%
“…Though experimental studies have shown adsorption-induced metal-insulator transitions, 7,8 reversible opening of a band-gap 9,10 and even ferromagnetic hysteresis, 11 the necessary precise control on the hydrogenation process has yet to be achieved. Hydrogenation of graphite has been studied in a number of experimental works, 3,[12][13][14][15][16][17][18][19][20][21][22][23][24] with a variety of surface-science techniques including thermal desorption, high-resolution electron-energy-loss spectroscopy, scanning tunneling microscopy, low-energy electron diffraction, angle a) Electronic mail: matteo.bonfanti@unimi.it b) Electronic mail: rocco.martinazzo@unimi.it resolved photo-emission spectroscopy, and X-ray photoemission spectroscopy. It has now been well established that sticking is an activated process, with a barrier related to the surface reconstruction accompanying the sp 2 → sp 3 re-hybridization of the carbon atom involved in the bond formation process.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, semihydrogenated layers might be accessible when one side of the Bi film is protected by a substrate and the other one is exposed to hydrogen. For graphene, half-hydrogenated layers have been successfully fabricated [50].…”
mentioning
confidence: 99%